2016
DOI: 10.1002/jmv.24587
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus species and clinical characteristics in the first wheezing episode in children

Abstract: The clinical data on the first wheezing episodes induced by different rhinovirus (RV) species are still limited. We aimed to investigate the prevalence of RV genotypes, sensitization status and clinical characteristics of patients having a respiratory infection caused by either different RV species or other respiratory viruses. The study enrolled 111 patients (aged 3–23 months, 79% hospitalized, 76% with RV infection) with the first wheezing episode. RV-specific sequences were identified by partial sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 44 publications
(101 reference statements)
3
26
0
1
Order By: Relevance
“…Additional studies with RV have demonstrated increased rates of atopic sensitization following infection [33][34][35]. In a cohort of 111 patients aged 3 to 23 months with wheeze, atopic sensitization was noted in 23% of all patients; further, RV infection was positively associated with age and other atopic factors including blood eosinophil count, eczema, cough duration and parental allergic rhinitis [33].…”
Section: Atopic Sensitization In Early Life and Environmental Exposuresmentioning
confidence: 98%
“…Additional studies with RV have demonstrated increased rates of atopic sensitization following infection [33][34][35]. In a cohort of 111 patients aged 3 to 23 months with wheeze, atopic sensitization was noted in 23% of all patients; further, RV infection was positively associated with age and other atopic factors including blood eosinophil count, eczema, cough duration and parental allergic rhinitis [33].…”
Section: Atopic Sensitization In Early Life and Environmental Exposuresmentioning
confidence: 98%
“…Rhinoviruses (RVs) are RNA viruses belonging to the family Picornaviridae genus Enterovirus , which has been classified into 3 species (A to C) with over 160 serotypes 64–67 . RVs are small single‐stranded RNA viruses with an icosahedral symmetrical capsid 68 .…”
Section: Rhinovirus and Its Diagnostic Approachesmentioning
confidence: 99%
“…RVs are the most frequent cause of respiratory tract infections in both children and adults. RV‐A and RV‐C are common RV species causing lower airway illness, wheezing and acute asthma, and they can lead to more severe symptoms than RV‐B in children 67,69 …”
Section: Rhinovirus and Its Diagnostic Approachesmentioning
confidence: 99%
“…The sequencing of 5′ NCR was performed as previously described (25). The amplification and sequencing method for VP4/VP2 region is also described in a recent publication (28). …”
Section: Methodsmentioning
confidence: 99%